Prevalence of osteoporosis in patients with nephrolithiasis and vice versa: a cumulative analysis - Jia, Shunjie; Liao, Jian; Wang, Yucheng; Zheng, Wenbiao; Jin, Jinghua; Xu, Weifang; Zheng, Qi (Frontiers in Endocrinology, 2023)
Purpose Nephrolithiasis is thought to be a risk factor for osteoporosis, but data assessing if osteoporosis predisposes to the risk of nephrolithiasis are lacking. The present study aims to investigate whether patients with nephrolithiasis have a prominently higher prevalence of osteoporosis than the controls and vice versa via a cumulative analysis. Methods Four databases were used to detect the eligible studies. We calculated the relative risk (RR) with a 95% confidence interval (CI) to assess the combined effect. The methodologies for conducting this study followed the PRISMA guidelines and were registered in the PROSPERO. Results Nine case-control or cohort studies with a total of 454,464 participants were finally included. Combined results indicated that there was a significantly higher prevalence of osteoporosis in patients with nephrolithiasis as compared to the general population without nephrolithiasis (overall RR from six studies= 1.204, 95%CI: 1.133 to 1.28, P< 0.001; heterogeneity: I2= 34.8%, P= 0.162). Conversely, osteoporosis was significantly correlated to an increased risk of nephrolithiasis as compared to the controls without osteoporosis (combined RR from four studies= 1.505, 95%CI: 1.309 to 1.731, P< 0.001; I2= 89.8%, P< 0.001). Sensitivity analysis on the two categories validated the above findings. No significant publication bias was identified in this study. Conclusions The present study highlighted a significantly high prevalence of osteoporosis in patients with nephrolithiasis and vice versa. This reciprocal association reminded the clinicians to conduct a regular follow-up assessment of bone marrow density or ultrasound when managing patients with nephrolithiasis or osteoporosis, especially for the elderly.